2008
DOI: 10.1007/s11869-009-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential and combined impacts of extreme temperatures and air pollution on human mortality in south–central Canada. Part II: future estimates

Abstract: This paper forms the second part of an introduction to a synoptic weather typing approach to assess differential and combined impacts of extreme temperatures and air pollution on human mortality, focusing on future estimates. A statistical downscaling approach was used to downscale daily five general circulation model (GCM) outputs (three Canadian and two US GCMs) and to derive six-hourly future climate information for the selected cities (Montreal, Ottawa, Toronto, and Windsor) in south-central Canada. Discri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 24 publications
1
51
0
1
Order By: Relevance
“…Makar et al, 2009) and ozone deposition (Engardt, 2008;Van Dingenen et al, 2009;Stella et al, 2011). The human-health impact of air pollution is one of the main drivers behind research in this field, with potentially substantial health effects resulting from climatechange-induced changes in air-quality (Sheffield et al, 2011;Chang et al, 2010;Tagaris et al, 2009Tagaris et al, , 2010Cheng et al, 2009;Jackson et al, 2010). Global financial losses due to reductions in crop yields resulting from ozone deposition are expected to reach between $1 billion to $17 billion, depending on the emissions scenario employed (Averny et al, 2011).…”
mentioning
confidence: 99%
“…Makar et al, 2009) and ozone deposition (Engardt, 2008;Van Dingenen et al, 2009;Stella et al, 2011). The human-health impact of air pollution is one of the main drivers behind research in this field, with potentially substantial health effects resulting from climatechange-induced changes in air-quality (Sheffield et al, 2011;Chang et al, 2010;Tagaris et al, 2009Tagaris et al, , 2010Cheng et al, 2009;Jackson et al, 2010). Global financial losses due to reductions in crop yields resulting from ozone deposition are expected to reach between $1 billion to $17 billion, depending on the emissions scenario employed (Averny et al, 2011).…”
mentioning
confidence: 99%
“…Within-decile mean mortality residuals in the bottom deciles were usually lower than those of the top deciles for all pollutants except for CO. In addition to this decile analysis, within-"other"-weather-group regression results also show that only air pollutants other than weather variables are significantly associated with elevated mortality, with a model R 2 of 0.71, 0.62, 0.40, and 0.30 for Montreal, Ottawa, Windsor and Toronto, respectively (refer to a companion paper-Part II, Cheng et al 2009 for details on regression). This finding is consistent with that of previous studies (Lambert et al 1998;Toronto Public Health 2001;Vedal et al 2003), which concluded that 1954 1959 1964 1969 1974 1979 1984 1989 1994 Fig.…”
Section: Mortality Baselinementioning
confidence: 80%
“…The study could enhance our understanding of environmental problems related to human health. To support the recommendation of adaptation policies to reduce risks to vulnerable populations due to climate change, it is necessary to estimate possible changes in future extreme temperature-and air pollution-related mortality, which is the major objective of a companion paper (Part II, Cheng et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding this notion, most projections of heat wave damages have previously been derived from the statistics of excess deaths based on observed data for vulnerable regions. Based on these predictions, a substantial increase in excess deaths has been deduced for the United States [21], Canada [22], Europe [23], United Kingdom [24], Australia [25], and other regions globally. Most of these studies, however, have not considered the aging demographics and related increases in heat vulnerability.…”
Section: Introductionmentioning
confidence: 99%